Effect of contact number on heat extraction of particle material for hydrogen production. (8th April 2023) - Zhang, Kai; Zheng, Bin; Sun, Peng; Shen, Yingkai; Gao, Tengfei; Wang, Youtang; Meng, Jian; Qi, Chenglu; Wang, Mingchao
Abstract: Hydrogen production by steam thermal reforming with waste heat of industrial particle material is of good prospects. But the insufficient research on the heat extraction traits of particulate matter has set up obstacles to its application. This paper focused on the effect of contact number, as it has not yet been fully studied. A series of steady-state numerical models based on a face-centered cubic packing was established to simulate the effect of contact number by removing selected particles. The results show that the contact number has a marked influence on the thermal resistance. As the contact number decreases by 12, the thermal resistance increases by 13.9∼31.9%. The removal of particles causes redistribution of heat transfer in different heat transfer modes. The heat transfer from the solid layer to the next layer decreases by 57.8% at most, and the radiation heat transfer between them is strengthened (36% at most). The effect of heat redistribution due to the removal of particles is significantly weakened after the heat flows through the first particle layer without removal operation. With these results, a better interpret of particulate matter heat extraction may be established. Graphical abstract: Image 1 Highlights: Effect of contact number on the heat transfer of the packed bed is studied. The physical model is constructed by removing selected particles. Temperature, heat flow characteristics and the heat transfer ratio are analyzed. The reduction in the contact number increases the overall thermal resistance. Removing particles causes redistribution of heat transfer modes.